1992
DOI: 10.1111/j.1699-0463.1992.tb00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profiles as an epidemiological marker in Salmonella enterica serovar berta infections

Abstract: Plasmid profiles of 674 Salmonella berta strains isolated in the period 1985–1989 from 674 cases of human infections were recorded. Five hundred and eighty‐nine of the strains examined (87.4%) contained plasmids and the mean number of plasmids was 1.8 per strain. Sixteen different plasmid sizes were recognized, 13 of which had also been reported from S. berta of poultry origin. The plasmids formed 90 different profiles. Forty‐five of these profiles, comprising 90.7% of isolates, had previously been recorded am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
0
26
1
1
Order By: Relevance
“…shown that a clear succession in plasmid profile types occurred during the outbreak [1,3]. In a search for more stable markers, we [6] and others [7], have further shown that geographically diverse strains of Berta showed surprisingly little chromosomal restriction fragment variation, and suggested that the serotype consists of a single clone of bacteria.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…shown that a clear succession in plasmid profile types occurred during the outbreak [1,3]. In a search for more stable markers, we [6] and others [7], have further shown that geographically diverse strains of Berta showed surprisingly little chromosomal restriction fragment variation, and suggested that the serotype consists of a single clone of bacteria.…”
Section: Introductionmentioning
confidence: 53%
“…The origin and year of isolation of Berta strains used (Table 1) have previously been reported [1,3,6]; strains investigated originated from poultry, humans, cattle, pigs and slurry during the outbreak in Denmark. The collection also contained control strains obtained from poultry and humans in six other countries.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonella enterica has long been recognized as an important source of food-borne infections and has commonly been associated with the consumption of contaminated poultry and poultry products (Olsen et al, 1992;Baggesen and Wegener, 1994). The global increase in human infections with serovar Enteritidis observed in the late 1980s and early 1990s (Rodrigue et al, 1990) was almost entirely attributable to the presence of this organism within the poultry production industry.…”
mentioning
confidence: 99%